2001
DOI: 10.1095/biolreprod64.4.1080
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Is a Putative Autocrine Regulator of the Rat Ovarian Theca Cell Compartment

Abstract: Apolipoprotein (apo) E inhibits androgen production by ovarian theca cells. We found that apo E, as a synthetic peptide mimicked the full-size protein, induced theca and interstitial cell (TIC) apoptosis indicated by pyknotic cell morphology, increased DNA end-labeling (TUNEL), and DNA ladders. None of the low-density lipoprotein (LDL) receptor superfamily members were involved because the universal antagonist of these receptors, receptor-associated protein (RAP), did not block apo E-induced apoptosis. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…This is in agreement with an earlier report from isolated theca/interstitial cells cultured from immature rats [23]. The combined in vivo and in vitro results reported here support the conclusion that VCD-induced follicle depletion results in an interstitial cell-enriched ovary that produces androgen in response to LH when insulin is also present.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with an earlier report from isolated theca/interstitial cells cultured from immature rats [23]. The combined in vivo and in vitro results reported here support the conclusion that VCD-induced follicle depletion results in an interstitial cell-enriched ovary that produces androgen in response to LH when insulin is also present.…”
Section: Discussionsupporting
confidence: 93%
“…Cells from these animals produced androstenedione, ranging from 10-13 ng/ml-g DNA per culture well, with no apparent sensitivity to LH. Interstitial cell androgen production is responsive to insulin [23]. Therefore, insulin was added to culture media to test its impact on progesterone and androstenedione production (Figs.…”
Section: Cell Culture Steroidogenic Productionmentioning
confidence: 99%
“…Results of this study show for the first time that 1) LH stimulates Akt phosphorylation in cultured bovine theca cells, and that 2) activation of PI3K/Akt is involved in CYP17A1 mRNA expression and androgen production in theca cells. Reportedly, LH induced Akt phosphorylation in whole rat ovary [21], and the PI3K inhibitor, LY294002, suppressed androstenedione production by theca cells in rat [22] and cattle [11]. It is possible that LH-stimulated Akt phosphorylation in theca cells is responsible for these observations reported earlier.…”
Section: Discussionmentioning
confidence: 93%
“…These results indicate that the deletion of Apoe has an obvious influence on ovarian follicle development. Previous studies have demonstrated that intraovarian APOE can control the production of 148 T Zhang, P Dai and others androgen in theca cells (Zerbinatti et al 2001). Therefore, the level of androgens in the Apoe K/K mice may exceed that in the WT mice.…”
Section: Discussionmentioning
confidence: 99%